Numerical investigation of laterally loaded pile groups at the crest of slopes - Meen-Wah Gui; Alex A. Alebachew (Scientific Reports)
Abstract Pile group foundations are widely used to support tall structures on both level and sloping terrain. However, predicting the lateral response of pile groups near slopes remains challenging due to complex soil-pile interactions that differ significantly from those on level ground. This study employed 3D finite element (FE) analysis using COMSOL v5.6 to investigate the behavior of laterally loaded $$2 × 2$$ pile groups positioned on the crest of slopes. Key variables included pile spacing (s/D = 3 to 6), slope gradient (1:1 to 1:2.5), and setback distance from the slope crest (b/D = 0 to 12). The results revealed critical insights. A setback ratio $$b/D \le 12$$ reduced lateral capacity by 15–35% compared to level ground, establishing $$b/D=12$$ as a critical threshold for design. Steep slopes (1:1) degraded lateral capacity by 5–20% compared to gentle slopes (1:2.5), highlighting the sensitivity of pile performance to slope steepness. Wider spacing (s/D = 6) improved lateral resistance by 40–50% over tightly spaced groups (s/D = 3) due to reduced group interaction effects. The lateral capacity of pile groups near slopes was governed by the sliding resistance of the passive soil wedge adjacent to the slope, analogous to a stabilizing berm in retaining wall design. The findings emphasize that setback distance is the most influential design parameter, followed by slope gradient and pile spacing. This study provides actionable guidelines for optimizing pile group configurations near slopes, ensuring safer and more economical designs.